Pengembangan Media Audio Visual pada Kompetensi Dasar Memahami Jenis-Jenis Alat Berat pada Pekerjaan konstruksi di SMK Negeri 1 Sitolu Ori - Satulo Buulolo; Envilwan Berkat Harefa; Aprianus Telaumbanua; Arisman Telaumbanua (Departement of Mathematics Education, 2023)
The purpose of this research is to develop audio visual media on basic competencies in understanding types of heavy equipment in construction work, which are valid, practical and effective. the type of research used is development research. The development model used is the Addie model, in this Addie model has five steps, namely Analysis, Design, Development, Implementation, and Evaluation. However, this research was only carried out until the development stage. Implementation, and Evaluation. In the development of audio-visual media, it was validated by several experts, namely, material experts, media experts and language experts and then tested on individual trials, small group trials, field trials and conducting evaluations or assessments of students. Based on the results of the research, the audio-visual media developed has been tested to be very valid by material experts by 97%, media experts by 95% by language experts by 93%, furthermore, audio-visual media is also very practical to use by students with a practicality percentage of 95%. The module is also very effective in use with a completeness percentage of 90%. From the results of the research above, the audio visual media in the basic competencies of understanding types of heavy equipment in construction work at SMK Negeri 1 Sitolu Ori has met the hopes and objectives of the researchers.